Effect of Modified Cassava Flour Lentil Date Biscuits on the Blood Glucose Level of Type 2 Diabetics - Fatmah (Pakistan Journal of Nutrition, 2016)
Background: Type 2 diabetes mellitus can be managed through pharmacological and non-pharmacological therapies. One non-pharmacological approach is consumption of foods with low glycemic index value to maintain normal blood glucose level. Objective: The objective of the current study was to assess the effect of consuming biscuits made with modified cassava flour, lentils and dates on the blood glucose status of diabetic patients. Materials and Methods: A randomized controlled trial, pre-post test design was completed with 141 subjects with type 2 diabetes which were divided into four groups fed biscuits made of modified cassava flour, lentils and dates (Caromma), modified cassava flour, tempeh and dates (Catemma), tempeh and dates (Temma), or dates only (Bisma) over a 4 weeks period. Anthropometric collected data included the intake of energy, protein, carbohydrates and fat and then blood glucose was examined before and 2 h after eating biscuits at the beginning, in the middle and at the end of the study. Results: Caromma biscuits were found to contain slightly higher levels of carbohydrates, zinc and vitamin A than the other three types and produced a low glycemic index value (<50). Increased post-prandial blood glucose was found 2 h after consumption of biscuits was the lowest in the Caromma group (6.4 points) compared with another three control group Caromma at the end of the study; blood glucose levels were also significantly different for the Caromma group before and after the study. Conclusion: Thus, it can be concluded that Caromma biscuits are safe for diabetic patients.